Climate Information Services Research Initiative: Final Report - Blumenstock, Ali (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Throughout Sub-Saharan Africa, smallholder farmers are at the frontlines of an increasingly variable and changing climate. Frequent and severe climate shocks and stresses threaten farmers’ lives and livelihoods, challenging the role agriculture could play in promoting economic growth, food security, poverty reduction, and community resilience. Timely, accurate, and useful farmer-focused weather and climate information services (CIS) can lessen these vulnerabilities by informing decisions of smallholder farmers to manage those climate risks. Valuable research exists on the impact of climate variability and change on farmers and the types of climate-related information farmers need for decision-making. However, critical gaps limit the understanding of how climate information services can best meet the decision-making needs of farmers, and the factors that most influence the effectiveness – delivery, uptake, and use – of climate information services. In response to these gaps, the United States Agency for International Development (USAID) funded the Learning Agenda on Climate Services in Sub-Saharan Africa, which included the Climate Information Services Research Initiative (CISRI) project. CISRI sought to generate knowledge and evidence to inform the development of climate information services that effectively meet African farmers’ decision-making needs in a variable and changing climate. This was accomplished through desk research, field-based research, collaboration with local and national partners, and pilots of new methodologies and approaches. The project was led by Mercy Corps in consortium with several partners, including the Humanitarian Response and Development Lab at Clark University (HURDL), the International Research Institute for Climate and Society at Columbia University (IRI), CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), World Agroforestry Centre (ICRAF), Practical Action, and Catholic Relief Services (CRS). The research undertaken by the CISRI consortium focused on synthesizing and analyzing existing knowledge on climate information services programs, and identifying gaps and inefficiencies in climate information services systems. In addition, CISRI developed innovative approaches to strengthening climate information services systems and evaluating the uptake and effectiveness of climate services. The project highlighted that CIS in Sub-Saharan Africa will only succeed in addressing the risks created by a variable and changing climate if users and their needs are involved as a critical component in all aspects of the CIS system. Considering climate information services as a system in which users are one of the vital elements is key for improving CIS moving forward. Otherwise, climate information services cannot effectively benefit those who are most vulnerable to climate risks. Through the CISRI project, the consortium generated research, methodologies, and learning to inform how climate information services can best meet the decision-making needs of farmers, and the factors that most influence its effectiveness. This will contribute to a better understanding of how to improve the design of climate information services programs moving forward, ultimately advancing the impact of future development investments on the livelihoods of farmers in Sub-Saharan Africa.